Economic Liberalization in Nepal: Determinants, Structure, and Trends of FDI - Bista, Raghu Bir (Bina Nusantara University, 2017)
This research examined the relationship between FDI (Foreign Direct Investment) and GDP (Gross Domestic Product) along with the impact of FDI determinants on FDI inflow in Nepal. This research used literature review by doing multiple regression models. This research used an econometric model based on Cobb Douglas Production Model and a theoretical growth model based on Solow Growth. The result indicates the positive relationship between GDP and FDI. Furthermore, liberalization and privatization policies are positive, but insecurity is disturbing.